Strategic Digital Water Resources Management: Challenges and Opportunities in the Period of Industrial Transformation and Climate Change - Ahmad Anaraki Mohammadi (Water Harvesting Research)
The advancement of industries and the impacts of climate change are among the primary drivers of the critical challenges the world faces today. This paper reflects a profound connection to the lessons of ancient civilizations, emphasizing the importance of sustainable practices. It addresses both the necessity and the barriers to integrating digital technologies into industrial activities. While the task was highly systematic, it was carried out using reputable databases, and this article highlights some of those efforts. Using VOS Viewer software, a total of 700 articles were analyzed, with a specific focus on titles and studies published between 2023 and 2025. Nowadays, the use of Artificial Intelligence (AI) and the Internet of Things (IoT) adds significant value to optimizing water resource management. However, even the most advanced technologies and systems—designed to identify users’ water consumption patterns and provide detailed analysis and data—come with their own set of challenges. Key issues such as inadequate technological infrastructure, resistance to change, and financial constraints are critical areas that need to be addressed to improve water management practices. Without a clear strategy and proper preparation—including a thorough understanding of contemporary needs and advanced conditions—efforts to design and outline effective solutions will fall short. Where there is sufficient internal capacity and a robust organizational structure, there is no reason why innovative, non-bureaucratic approaches, such as targeted recommendations, should not be considered to address water-related challenges and engineer sustainable solutions.